Manajemen Sarana Dan Prasarana: Persepsi Siswa Terhadap Kualitas Pelayanan Administrasi Sekolah - Syaputra, Helmi; Irawati, Irawati; Setyaningsih, Rini (Universitas Pakuan, 2023)
FACILITIES AND INFRASTRUCTURE MANAGEMENT: STUDENTS' PERCEPTIONS OF THE QUALITY OF SCHOOL ADMINISTRATIVE SERVICESFacilities and infrastructure management is the management and supervision of facilities and infrastructure in schools. With good management of facilities and infrastructure, the facilities and infrastructure in schools can contribute more optimally to the quality of services in schools. The successful quality of administrative services in schools is supported and influenced by the utilization of all educational facilities and infrastructure in schools effectively and efficiently. This research aims to find out how much influence students' perceptions of the management of facilities and infrastructure have on the quality of service at SMA Negeri 1 Bangkinang and also see factors that can influence these two variables. This research is a quantitative research using simple linear regression analysis research techniques which examines the influence of students' perceptions of facilities and infrastructure management (X) on the quality of administrative services (Y) at SMA Negeri 1 Bangkinang. This research aims to see how much influence students' perceptions of facilities and infrastructure management have on the quality of service at SMA Negeri 1 Bangkinang. The population in this study was 300 people, namely students, taking a sample of 30% of the population, namely 90 people. The sampling technique used is Simple Random Sampling using analysis assistance from the SPSS Statistics 23 application. The results of the research show that there is a significant influence between students' perceptions of facilities and infrastructure management on the quality of service at SMA Negeri 1 Bangkinang with a significance level of 5%, namely 0, 2681 (0.779 0.2681). And the calculation result of the coefficient of determination (R Square) is 0.607. The calculation result of the coefficient of determination (R Square) is 60.7%. Meanwhile, the remaining 39.3% (100%-60.7%) was influenced by other variables not included in this study. Schools are expected to always carry out ongoing evaluations to improve the quality of services at SMA Negeri 1 Bangkinang.